Extrusion film casting of long chain branched polypropylene. Issue 9 (14th November 2014) - Chikhalikar, Kalyani; Banik, Sourya; Azad, Lal Busher; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Doshi, Pankaj; Pol, Harshawardhan; Lele, Ashish
<x xml:space="preserve">Abstract</x> Extrusion film casting (EFC) is an important melt processing operation which is extensively used to make polypropylene (PP) films. Linear PP shows significant amount of necking and draw resonance during EFC. One of the ways to reduce necking is to introduce long chain branches (LCB) on the polymer backbone. The long branches impart extensional strain hardening behavior thereby stabilizing the melt flow. In this work, we investigate the influence of long chain branching in polypropylene on the extent of necking in the EFC process. Laboratory scale EFC experiments were performed on homopolymer PP of linear and long chain branched architectures. Simulations of the EFC process were carried out using the one‐dimensional flow model of Silagy et al., Polym. Eng. Sci., 36, 2614 (1996) into which we incorporate two different multi‐mode molecular constitutive equations namely, the 'eXtended Pom‐Pom' equation (XPP, for long chain branched PP) and the 'Rolie‐Poly' equation (RP‐S, for linear PP). Our experimental data confirm that presence of long chain branching in PP reduces the extent of necking and our numerical predictions show qualitative agreement with experimental data, thereby elucidating the role of chain architecture on the extent of necking. POLYM. ENG. SCI., 55:1977–1987, 2015. © 2014 Society of Plastics Engineers